An Econometric Model of Nigeria's Financial Sector. - Ikhide, Sylvanus Ihenyen (Obafemi Awolowo University, 2014)
This study has attempted to construct a model for the financial sector of the Nigerian economy. Three subsectors were identified - the commercial banks, the non-bank public and the monetary authorities. Using data collected on a quarterly basis from the economy between 1968 and 1983, equations were formulated to explain the behaviour of these sectors within a general portfolio analysis.